PENGARUH SUHU, WAKTU, DAN KONSENTRASI LARUTAN NATRIUM BIKARBONAT TERHADAP PENCUCIAN ISOEUGENYL ACETATE - Widyawati, Yeti; Wahyudin, Muhammad; Zakaria, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): Juni, 2019)
Isoeugenyl acetate is an eugenol derivative product in the form of white crystalline powder, it smells like vanilla, and has a spicy, hot and slightly sweet taste. Isoeugenyl acetate used in various industries, such as pharmaceuticals, cosmetics, food and beverages, cigarettes, pesticides, fishery, mining, packaging and other chemical industries. However, there is a problem in the product specification that is unacceptable to the consumer that is the acid number is high,  it;s make of smell of acids in the product. Standart product of isoeugenyl acetate has an acid number of 0.5 mgKOH/g. The research method used to decrease the acid number in isoeugenyl acetate is washing process. The aim of of this research are to obtain temperature, stirring time and the concentration of sodium bicarbonate. The condition of washing process of isoeugenyl acetate were obtained at temperature 35oC, stirring time 100 minutes, and concentration sodium bicarbonate 3,5%. In these conditions acid number of 0.4594 mgKOH/g and  the drying time of the isoeugenyl acetate product of 7 hours. Keywords : Isoeugenyl acetate, sodium bicarbonate, Acid number